Association of Alpha Haemoglobin Stabilizing Protein in HbE/ Beta-Thalassaemia Patients in Malaysia - Lim, Wai Feng (2011)
β-thalassaemia is a condition caused by the quantitative reduction or absence of β-globin chain synthesis due to β-globin gene mutations. It leads to excessive unpaired α-globin chains precipitates which causes membrane damage and ineffective erythropoiesis. Haemoglobin /β-thalassaemia patients have a remarkable variability in clinical severity due to globin chain imbalance and effects of other modifiers. Alpha haemoglobin stabilizing protein (AHSP) is an abundant erythroid protein that binds specifically to free α-globin chains to prevent its precipitation. Studies suggest that partial or full knockdown of AHSP may exacerbate β-thalassaemia phenotype in humans. This study was done to investigate the association between AHSP and HbE/β-thalassaemia patients in Malaysia. Peripheral blood samples from 105 patients were collected. Full blood count analysis and HPLC were carried out on the peripheral blood. Patients with transfusions less than three months were excluded. In the end, 30 selected samples without underlying iron deficiency or co-inheritance of α-thalassaemia or extra α-genes were genotyped with ARMS PCR for common β-globin mutations and rare β-globin mutations were detected through sequencing. Common AHSP sequence variants were typed by tetra-primer ARMS PCR. TaqMan® quantitative RT-PCR was employed to correlate the AHSP expression to the severity and globin expression levels of HbE/β-thalassaemia. AHSP expression among 30 HbE/β-thalassaemia patients varied up to 4.50-log differences which was negatively correlated to MCH (p=0.009) and HbF (p=0.002), while positively correlated to alpha-globin expression level (p=0.003), betaglobin expression level (p=0.001) as well as excess alpha globins (p=0.004). The significant correlation between AHSP with MCH and HbF showed that AHSP increases when there are more unpaired α-globin chains. My study suggests that AHSP is a secondary compensatory mechanism to balance the excess α-globin chains in β-thalassaemia after the formation of HbF. This study further strengthens the theory that AHSP is a modifier for phenotypic severity in HbE/β-thalassaemia patients.